A retrospective multicenter study of carbon‐ion radiotherapy for external auditory canal and middle ear carcinomas. (8th December 2018) - Hayashi, Kazuhiko; Koto, Masashi; Demizu, Yusuke; Saitoh, Jun‐ichi; Suefuji, Hiroaki; Okimoto, Tomoaki; Ohno, Tatsuya; Shioyama, Yoshiyuki; Takagi, Ryo; Ikawa, Hiroaki; Nemoto, Kenji; Nakano, Takashi; et al.
Abstract: Background: We conducted a retrospective multicenter study to assess the clinical outcomes of carbon‐ion radiotherapy (CIRT) for head and neck malignancies (Japan Carbon‐Ion Radiation Oncology Study Group [J‐CROS] study: 1402 HN). We aimed to evaluate the safety and efficacy of CIRT in patients with external auditory canal (EAC) and middle ear (ME) carcinomas. Methods: Thirty‐one patients treated with CIRT at four Japanese institutions were analyzed. Fourteen patients (45.2%) had squamous cell carcinomas, 13 (41.9%) had adenoid cystic carcinomas, and four (12.9%) had other types. Nineteen (61.3%), six (19.4%), three (9.7%), and three (9.7%) patients had T4, T3, T2, and T1 disease, respectively. All patients had N0M0 status. The median radiation dose was 64 Gy (relative biological effectiveness) in 16 fractions. The median gross tumor volume was 33.3 mL. Results: The median follow‐up period was 18.4 months (range, 5.1‐85.6). The 1‐ and 3‐year local control and overall survival rates were 75.0% and 55.0% and 79.3% and 58.7%, respectively. Regarding grade 3 or higher toxicities, three patients (9.7%) had grade 3 dermatitis, one (3.2%) had grade 3 mucositis, and two (6.5%) had grade 3 central nervous necrosis (ie, radiation‐induced brain necrosis). No grade 4 or worse reactions were observed. Conclusion: CIRT was effective for EAC and ME carcinomas. Abstract : Carbon‐ion radiotherapy showed high local control rate (a), progression‐free survival rate (b) and overall survival rate (c).